2015
DOI: 10.1093/jee/tou007
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Expression of Antixenosis in Soybean to Anticarsia gemmatalis and Spodoptera frugiperda (Lepidoptera: Noctuidae)

Abstract: This study aimed to evaluate some factors that influence the expression of antixenosis in soybean genotypes against Anticarsia gemmatalis Hübner and Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae). Free-choice and no-choice feeding assays were performed with the resistant soybean genotype IAC 100 and the susceptible genotype BRSGO 8360 using A. gemmatalis and S. frugiperda larvae. The following factors that may affect expression of resistance were evaluated: one larva versus two larvae per leaf di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 16 publications
1
19
0
1
Order By: Relevance
“…as soon as they are synthesized by metabolic processes throughout plant development (Panda and Kush 1995). Upon preparation of leaf discs with a cork borer, rupture of cells or organelles storing the secondary metabolites probably occurred, resulting in their release and thereby greater exposure to insects during the course of the bioassay (Boiça Júnior et al 2015b). Effects were less pronounced in entire leaflets than leaf discs probably because larvae must first disrupt the structures storing defensive secondary compounds prior to being in contact with them.…”
Section: Discussionmentioning
confidence: 99%
“…as soon as they are synthesized by metabolic processes throughout plant development (Panda and Kush 1995). Upon preparation of leaf discs with a cork borer, rupture of cells or organelles storing the secondary metabolites probably occurred, resulting in their release and thereby greater exposure to insects during the course of the bioassay (Boiça Júnior et al 2015b). Effects were less pronounced in entire leaflets than leaf discs probably because larvae must first disrupt the structures storing defensive secondary compounds prior to being in contact with them.…”
Section: Discussionmentioning
confidence: 99%
“…Spodoptera frugiperda is a polyphagous species that infests cotton (Campos, Boiça-Júnior, Valério Filho, Campos, & Campos, 2012;Jesus, Boiça Junior, Alves, & Zanuncio, 2014), rice, millet, sorghum (Busato et al, 2004), soybean (Boiça Junior, Souza, Neves, Ribeiro, & Stout, 2015) and other crops. In Brazil, one of the factors that contribute to failures in the control of S. frugiperda is the large number of hosts caused by the succession of crops with different phenologies (Sá, Fonseca, Boregas, & Waquil, 2009;Barros, Torres, & Bueno, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to emphasize that although several studies related to the development and/or preferences of the Noctuidae insect family have been performed for soybeans Boiça Júnior et al 2015), there are no studies specifically concerned with the attractiveness of C. includens in relation to the genotype 'IAC 100' , which demonstrates the importance of the present research. Recent studies have identified 'IAC-100' as a good progenitor candidate for breeding intended to generate promising lineages that exhibit both insect resistance characteristics and high productivity (Maia et al 2009).…”
Section: Resultsmentioning
confidence: 98%